EXPLORING POTENTIAL AND INNOVATIVE STRATEGIES FROM ZIS FUND COLLECTION AT THE NATIONAL AMIL ZAKAH AGENCY IN SIAK DISCTRICT - Ilham, Arifin Muhammad; Ismail, Nurizal; Al-Ayubi, Solahuddin (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
The purpose of this research is to analyze the potential of zakah, infaq, and sadaqah (ZIS) in the Siak Regency area, and the innovative strategies carried out by BAZNAS Siak Regency in an effort to raise ZIS funds in the Siak Regency area. Triangulation qualitative methods are employed in this research. The findings show that zakah's potential in Siak Regency will be between Rp1,415,149.7075 billion and Rp2,434,057.4969 billion by 2022. In addition, the collection of zakah through BAZNAS Siak Regency is considered quite significant, with a potential range between 0.86% to 1.49% and an average of 1.25% based on the opinion of 2.5% of GRDP. However, if using the assumption of 4.3% of GDP, it ranges from 0.50% to 0.87% with an average of 0.73%. Even though there was a slight increase in zakah collections in Siak Regency in 2023, it ended up at Rp22,524,942,009. However, the GRDP data for Siak Regency in 2023 is not yet known, so the percentage ofachievement cannot be identifiedBAZNAS Siak Regency saw a positive increase in ZIS collection. ZIS collection experienced a significant increase from 2016 amounting to Rp9,908,684,571 until 2023 when it reached Rp25,046,486,280. BAZNAS Siak Regency uses a variety of innovative strategies to raise ZIS funds. This strategy includes the implementation of programs such as GEMAR Siak Berzakah, Establishment of New UPZ, SIKAH Program, Muzakki Services, Partnership Program (CSR/DSKL), and Zakah Campaign.